Single-Center Experience With the Thoraflex™ Hybrid Prosthesis: Indications, Implantation Technique and Results - Wisniewski, Konrad; Motekallemi, Arash; Dell'Aquila, Angelo M.; Oberhuber, Alexander; Schaefers, Johannes F.; Ibrahim, Abdulhakim; Martens, Sven; Rukosujew, Andreas (Frontiers in Cardiovascular Medicine, 2022)
Objective: The aim of this study was to evaluate the early and mid-term results after frozen elephant trunk (FET) procedure for the treatment of complex arch and proximal descending aortic disease in a single center institution. Methods: From April 2015 till July 2021, 72 patients (25 women, 60.4 ± 10.3 years) underwent Thoraflex™ Hybrid implantation at our institution. The indications were thoracic aortic aneurysm (n = 16, 22.2%), post-dissection aneurysm (n = 21, 29.2%), and acute aortic dissection (n = 35, 48.6%). Antegrade cerebral perfusion under moderate hypothermia (28°C) was employed in all cases. Eighteen patients (25%) have already been operated due to heart or aortic disease. Results: Overall In-hospital mortality was 12.5% (9 patients), rates of permanent neurological dysfunction and spinal cord injury were 9.7% and 5.5% respectively. In-hospital mortality rate among patients operated on acute aortic dissection, thoracic aortic aneurysm and post-dissection aneurysm were 8.6%, 6.2% and 23.8% respectively. Mortality at mean follow-up of 26 ± 20 months was 9.7%. 23 patients (31.9%) required a subsequent procedure in distal aorta: endovascular stentgraft extension in 19 patients (26.4%) and open aortic surgery in 4 patients (5.5%). The mid-term survival of type A aortic dissection patients was 97%. Conclusions: Our experience with the Thoraflex Hybrid prothesis demonstrates its surgical applicability for different types of aortic pathologies with promising outcomes during early and midterm follow-up. Our technique and perioperative management lead to comparable or even superior neurological outcomes and mortality in urgent cases considering other high volume centers.